1998
DOI: 10.1111/j.1399-302x.1998.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of salivary immunoglobulin A antibody and initial mutans streptococcal infection

Abstract: We explored the relationship between mutans streptococcal infection and the development of salivary IgA antibody during initial colonization. Repetitive swabbing (n = 292) of the teeth of 33 children revealed that 45% became infected with mutans streptococci between 13 and 36 months of age. In contrast, mutans streptococci could not be detected in 18 children whose last sample was taken at 39-81 months of age (median age = 62 months). During the period of mutans streptococcal infectivity, immunoglobulin A (IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
15

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 23 publications
1
56
1
15
Order By: Relevance
“…This contradiction is probably because the source of transmission is very variable, depending on behavior: the frequency of salivary contact between mother and child and a mother's salivary MS level mutans streptococci (16) and cultural and environmental conditions of the population studied (8,18,24). Furthermore, variability in transmission can be associated with children's individual susceptibilities, including the period defined as a window of infectivity (5), which was reported to be earlier in Brazilian children (27); the number of erupted teeth (3,5); the emergence of molars (5); the presence of enamel hypoplasia (23); sucrose consumption (27); the action of unspecific factors of the salivary and mucosal immune systems (21); and immunological conditions in children (32).…”
Section: Discussionmentioning
confidence: 99%
“…This contradiction is probably because the source of transmission is very variable, depending on behavior: the frequency of salivary contact between mother and child and a mother's salivary MS level mutans streptococci (16) and cultural and environmental conditions of the population studied (8,18,24). Furthermore, variability in transmission can be associated with children's individual susceptibilities, including the period defined as a window of infectivity (5), which was reported to be earlier in Brazilian children (27); the number of erupted teeth (3,5); the emergence of molars (5); the presence of enamel hypoplasia (23); sucrose consumption (27); the action of unspecific factors of the salivary and mucosal immune systems (21); and immunological conditions in children (32).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, antibody blockage of an important adhesin epitope during the reconstruction of the dental biofilm following chlorohexidine treatment places indigenous mutans streptococci at an insurmountable competitive disadvantage for recolonization. An interesting parallel may be the observation that young children who do not become naturally infected with mutans streptococci during the "window of infectivity" remain undetectably infected for several years (Caufield et al, 1993;Smith et al, 1998a), potentially because its niche in the dental biofilm has been filled by other indigenous flora. Experimental passive immune protection could also be achieved with antibody to GTF (Hamada et al, 1991) or GbpB (Smith et al, 2001a).…”
Section: (B) Passive Immune Approachesmentioning
confidence: 99%
“…Protection can be achieved by either subcutaneous injection of GbpB in the salivary gland region (Smith and Taubman, 1996) or by mucosal application by the intranasal route (Smith et al, 1997a). Saliva samples from young children often contain IgA antibody to GbpB, indicating that initial infection with S. mutans can lead to natural induction of immunity to this protein (Smith et al, 1998a). Preliminary studies have shown that GbpA appears to be less immunogenic than GbpB and that its ability to induce protective immunity is problematic (Smith et al, 1997a).…”
Section: (C) Glucan-binding Proteinsmentioning
confidence: 99%
See 2 more Smart Citations